Application of digital Agricultural Tools in Indonesia: From Creativity towards Rural Community Innovation - Widaningsih, Neni; Sutiharni, Sutiharni; Istikomah, Istikomah; Mulyana, Mumuh; Ali, Helmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
After understanding the research questions, we directed the search for data electronically to writing a collection of journal publications, books, and websites. We cannot conclude reports of untested, substantiated review findings on the use of innovations in agriculture without first attempting to analyze the various kinds of literature that incorporate, among other things, coding frameworks, in-depth assessments, and concluding. We carried out this study with a phenomenological approach, which is a methodology that seeks to obtain the most extensive data and then for us to study and gain understanding and become valid and convincing findings. The reason is that this review uses discretionary data from various sources. Subjective data whose sources of information we take from various data published between 2010 and 2021. We use the Google Search application to search for information using keywords such as digital applications, modern horticulture, innovation, and progress in compiling agribusiness. Based on these data, we can report that the use of trend-setting innovation applications in the agricultural sector is a consequence of innovations from both public authorities and the regions themselves, thus giving birth to new advances where agribusiness currently cannot be separated from electronics. This is an innovation that makes efficient use of services in the office